The integration of Illyria into the Roman Empire (3rd century BC-1st century AD) - de Aquino Silva, Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2025)
This article aims to examine the integration of Illyrian territory into the Roman Empire. We demonstrate that the Roman conquest and occupation were slow and gradual processes, extending over centuries until the establishment of the province. Between the 3rd century BC and 1st century AD, Illyrian territory was the stage of disputes, and its integration was carried out through various Roman strategies, not only military but also political and legal. Furthermore, we note the influence of the natives in this process, either through direct resistance or through established agreements. Initially, we explore the ethnic and geographic composition of Illyria in the pre-Roman context, and then we discuss the phases of the annexation of the region into the Roman Empire, addressing the natives’ resistance and the role of local elites in the integration process.